Cover Image. (27th January 2020) - Li, Ningbo; Wang, Yijun; Liu, Feijun; Zhao, Xin; Xu, Xinhua; An, Quan; Yun, Keming
Abstract : The cover image is based on the Full Paper* Air‐stable zirconium(IV)‐salophen perfluorooctanesulfonate as a highly efficient and reusable catalyst for the synthesis of 3, 4‐dihydropyrimidin‐2‐(1H)‐ones/thiones under solvent‐free conditions by Ningbo Li https://doi.org/10.1002/aoc.5454 .***